Sosialisasi Akuntan Mengajar Dorong Minat Belajar Akuntansi Dan Membuka Pilihan Karir - Srimindarti, Ceacilia -; Hardiningsih, Pancawati -; Lisiantara, Greg. Anggana; Nuswandari, Cahyani - (LPPM Universitas Pekalongan, 2025)
The decline in student interest in accounting can be caused by various factors. Several factors behind the decline in student interest in accounting include a lack of understanding of the accounting profession, high competition with other fields, lack of promotion of the accounting profession, and the perception that accounting is only for people with a financial background. Several professional organizations and accounting educational institutions have attempted to further promote the benefits and opportunities in an accounting career. Various education and training programs have been developed to make accounting more relevant and attractive to the younger generation who are more digital and technology-oriented. The proposal for this community service program is motivated by the importance of opening students' insights into the prospects for a future profession in accounting which is still promising but also followed by always updating information technology. The socialization of teaching accountants was attended by 30 accounting students and teachers who took turns. Furthermore, the method used in this PKM is in the form of training and mentoring for approximately 2 months. After participating in training and mentoring, it is hoped that participants will have more open insights regarding the accounting profession, thereby increasing the number of students' interest in accounting. The expected output in this community service is in the form of scientific articles published in nationally reputable journals.